ANALISIS HUBUNGAN KARAKTERISTIK PASIEN DENGAN TINGKAT KEPUASAAN PELAYANAN KEFARMASIAN DI KLINIK SITI HADJAR KOTA TEGAL: Heni Purwantiningrum, Agus Susanto (JURNAL SMART ANKes, 2021)
Patient satisfaction is one thing that needs to be achieved in pharmaceutical services because patient satisfaction is one indicator of the success of a service. Patient satisfaction has many factors consisting of internal and external factors. One of the factors that influence satisfaction is the patient's sociodemography. The patient's sociodemography can be in the form of age, gender, education, and other factors inherent in the patient. In research activities, this is often referred to as the respondent's characteristics. This study aims to analyze the characteristics of the level of patient satisfaction at the Siti Hadjar Clinic, Tegal City. This study is a descriptive-analytic study with a cross-sectional design. The sample size of this study was 277 patients who were drawn using the simple random sampling method. The study was conducted at the Siti Hadjar Clinic in the period April-June 2021. Data were collected using a questionnaire instrument. The results showed that the majority of respondents felt very satisfied with the services of pharmaceutical, which was indicated by the mean value of 4.43. Test of the relationship between the five characteristics of respondents consisting of age, gender, education, type of work, and type of financing with patient satisfaction showed no significant relationship. All test results show a significant value above 0.05.